Hyperhemolysis Syndrome Following Pre-Operative Red Blood Cell Exchange. (28th October 2021) - Allison, D; Karimi, S S; Campbell-Lee, S
Abstract: Introduction/Objective: Pre-operative red blood cell exchange (RBCX) for patients with Sickle Cell Disease (SCD) is a category III indication. In our institution, RBCX is routinely performed pre-operatively when general anesthesia is necessary with the goal of HbS%<30 and reduction in adverse events related to general anesthesia. In the context of elective surgery, the risks and benefits of both the operation and any pre-operative transfusion must be discussed with the patient. Herein, we present an extreme case of Hyperhemolysis Syndrome resulting from a pre-operative RBCX. Methods/Case Report: A 23-year-old transgender female with SCD (Hb S Lepore) treated with Hydroxyurea presented for elective breast augmentation for gender-affirmation. Her pre-operative plan included a RBCX. Her pre-exchange hemoglobin (Hb) and hematocrit (Hct) were 10.3 g/dL and 29.3%, respectively. Hb electrophoresis revealed HbS 52%, HbF 41.4%, HbA2 7.4%, and HbA was not detected. Type and Screen (T&S) demonstrated O + blood group, with a negative antibody screen, and with no known historical alloantibodies. RBCX was performed using the Spectra Optia (TerumoBCT, Lakewood, CO, USA) with exchange volume of 1.9 L of group O+ RBCs, phenotypically matched for C, E, and K, an end Hct of 30% and an FCR of 30%. Her post-exchange Hb and Hct were 10.2g/dL and 29.5%, respectively. Hemoglobin fractionation revealed HbS 12% and HbA 73%. She underwent surgery without intraoperative complications. Two weeks post RBCX, her Hb had decreased to 5.3 g/dl, and her LDH and Total Bilirubin had increased to 253 ul and 1.8 mg/dl, respectively. A repeat T&S drawn 8 days after RBCX revealed a positive antibody screen and direct antiglobulin test (DAT). Three new alloantibodies were identified: anti-Fya (present in plasma and eluate); anti-Jkb (present in plasma); anti-S (eluate). She was treated with IVIG, 0.4 g/Kg/day for 5 consecutive days and 2 doses of subcutaneous darbepoetin 100 mcg and subsequently discharged with close outpatient follow up. Her Hb returned to baseline at 11 g/dL, 48 days post RBCX. Results (if a Case Study enter NA): N/A Conclusion: Pre-operative RBCX decreases morbidity in sickle cell patients undergoing general anesthesia. In the setting of elective surgery, patients must be counseled on the benefits and risks of surgery as well as the requisite RBCX. In our case, the patient developed multiple alloantibodies, with lifelong implications should she ever need future blood transfusions.